Chemical Effectiveness of Salvadora persica and Commercially Available Whitening Toothpaste on Preventing Tea and Chlorhexidine Stain (in vitro study) - Erlina Sih Mahanani; Erry Mochamad Arief; Puteri Ezdiani Binti Mohamed Ismail (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2011)
Salvadora persica, a plant that contains a wide range of healthy components, has been used as chewing stick for ages to maintain good oral hygiene and currently has been approved to remove stains. However, its stain-preventing effect is still under investigation. This study aimed to investigate the effectiveness of Salvadora persica and commercially available whitening toothpastes on preventing tea and chlorhexidine stains. Sixty clear acrylic blocks were used and divided into 3 groups, 20 for each group. First group was treated with drinking water, second with commercially available whitening toothpaste and third with whitening toothpaste containing Salvadora persica extract. Baseline measurement by spectrophotometer was taken before starting the procedure. All specimens were immersed in artificial saliva for 2 minutes, rinsed in distilled water and exposed in 0.2% chlorhexidine and tea solution. These cycles were performed 8 times a day for 5 days. Intervention with whitening toothpaste was done for 2 minutes; twice a day. Eventually, all blocks were removed, washed and dried. Stain was assessed by spectrophotometer and visual assessment using Lobene stain index (1968). This study results showed significant differences among groups (Kruskal-Wallis test, p<0.001) and Salvadora persica extract was found to be more effective than commercially availablewhitening toothpaste on preventing stain formation